Creating an interaction interface to improve user engagement in virtual reality systems. Issue 4 (4th July 2017) - Ray, Ananda Bibek; Deb, Suman; Devi, Suraksha
Abstract: Virtual Reality (VR) has come up as a pinnacle of the ground-breaking advances in computing power through developments in fields of electronics, software and mobile computing. VR systems were first introduced to target entertainment and gaming, but finds equal importance in educational and training purposes. The system used in our experiment takes help of Google's 'Cardboard' platform. Although very easy to operate, extremely cost effective and portable, it lacks a sophisticated input system to facilitate interaction between virtual world and the user. We design and implement a wearable device that enables the VR system to recognize user hand movement and gesture to allow manipulation of objects in the virtual world. We measure the effectiveness of above mentioned system by usability and acceptance testing in comparison to the existing interaction techniques. The effects on user engagement is also quantified and analysed. Through our experiments, we intend to establish that such a setup is preferred by users for regular usage and improves their level of interaction and participation.